Optimization of linear and nonlinear optical parameters of As40Se50Te10 thin films by thermal annealing. (August 2021) - Sahoo, D.; Priyadarshini, P.; Aparimita, A.; Alagarasan, D.; Ganesan, R.; Varadharajaperumal, S.; Naik, Ramakanta
Graphical abstract: Highlights: The linear (n) and nonlinear refractive index (n2 ) increased with annealing. The 3rd order nonlinear susceptibility (χ (3) ) increased. The optical as well as electrical conductivity and extinction coefficient increased. The optical band gap reduced with annealing with an increase in disorder. The electrical susceptibility decreased with annealing temperature. Abstract: The present study reports the linear and nonlinear optical properties of as-prepared and annealed As40 Se50 Te10 thin films prepared on glass substrate by thermal evaporation method. The modifications in different properties after annealing were studied by XRD, EDAX, Raman spectroscopy, FESEM and UV–Vis-NIR and XPS spectroscopy. The study reports the decrease in optical band gap due to increase in disorder while the width of the tail in the gap increased with annealing temperature. The linear refractive index, optical as well as electrical conductivity and extinction coefficient increased with annealing. The dispersion energy, oscillator energy, dielectric constant and oscillator strength increased with annealing temperature while the electrical susceptibility decreased upon annealing. The 3rd order optical susceptibility and nonlinear refractive index were found to be increased with annealing temperature. The influence of different annealing temperatures on the variation of different parameters were elaborately explained on the basis of defect states in localized region. The structure remained unchanged while the heteropolar to homopolar bond conversion was noticed from the XPS and Raman spectroscopy. The changes in both nonlinear and linear optical properties by annealing shows that annealing temperature can be used as an important tool for controlling the optical constants of As40 Se50 Te10 chalcogenide film which could be a suitable candidate for numerous photonic applications.